PERSEPSI MASYARAKAT KOTA DENPASAR ATAS RENCANA KEBIJAKAN EKSTENSIFIKASI CUKAI PADA MINUMAN BERPEMANIS - Dewi, Saabina Putri; Karmana, I Wayan; Dwijayanti , Ni Made Ayu (JURNAL PERSPEKTIF BEA DAN CUKAI, 2024)
The plan to impose an excise tax on sweetened beverages is driven by the negative impacts of excessive sugar consumption, which contributes to health issues such as obesity and diabetes. Other ASEAN countries have already implemented excise taxes on various products, including sweetened beverages, highlighting an untapped potential for Indonesia. This study aims to evaluate the public perception of the proposed policy to extend excise taxation to sweetened beverages, focusing on variables such as attitudes, motives, levels of importance, and expectations. This study analyzes primary data collected through questionnaires distributed to 100 respondents in Denpasar City. The variables were tested using descriptive statistical techniques, classical assumption tests, and hypothesis testing with the help of IBM SPSS Statistics 25 software. The results indicate that individuals with a positive attitude significantly support the proposed excise tax policy, whereas negative motives hinder support. Although the level of importance shows a positive influence, it is not strong enough to be the primary determining factor in supporting this policy. Expectations regarding the benefits and effectiveness of the policy have a positive and significant impact, suggesting that a positive perception of the policy outcomes drives public support. Based on the Theory of Planned Behaviour, attitudes, motives, levels of importance, and expectations directly influence individuals' intentions and behaviors in supporting this policy. Overall, this study suggests that the successful implementation of an excise tax policy on sweetened beverages requires effective communication efforts, addressing negative motives, and enhancing public expectations of the policy's benefits.